2012
DOI: 10.5536/kjps.2012.39.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids Digestibility of Corn Distillers Dries Grains with Solubles in Broiler Chickens

Abstract: To investigate the effects of dietary substituent of corn distiller's dries grains with solubles (CDDGS) on the amino acid digestibility of broiler diet, twenty four Ross broilers (6-wk-old) were used in this study. Basal diet (CP 19%, ME 3,150 kcal/kg) was formulated on corn-soybean meal and two levels of CDDGS (6 and 12%) were supplemented to basal diet. CDDDS levels (0, 6 and 12%) and 4 different sites of chicken intestines (distal end of jejunum, the middle part of the ileum, the distal end of ileum and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…One of the nutrients is protein. Several studies have reported that fresh maggot contains high protein reaching 19.26-63.99% [1,3,5,6], so it is potentially used as an alternative source of animal protein for fish and poultry to overcome rather expensive feed costs [7]. Hanim et al [2] have stated that organic matter containing protein > 19.00% can be classified as a source of protein.…”
Section: Introductionmentioning
confidence: 99%
“…One of the nutrients is protein. Several studies have reported that fresh maggot contains high protein reaching 19.26-63.99% [1,3,5,6], so it is potentially used as an alternative source of animal protein for fish and poultry to overcome rather expensive feed costs [7]. Hanim et al [2] have stated that organic matter containing protein > 19.00% can be classified as a source of protein.…”
Section: Introductionmentioning
confidence: 99%
“…Sumado a lo anterior, los nutrientes que contiene esta harina en relación con la materia seca, proteína cruda, fibra cruda, extracto etéreo y cenizas son similares a los reportados en harina de soja o pescado (Pretorius, 2011); resultando una excelente fuente nutricional que favorece el desarrollo de las aves durante todas las etapas de producción. Además, se ha demostrado que la suplementación con harina de larvas de mosca no induce a enfermedades como la erosión o la molleja, no muestra toxicidad en el tracto gastrointestinal de las aves y no genera estrés en los órganos de los pollos de engorde (Hwangbo et al, 2009).…”
Section: Introductionunclassified
“…Many studies report the chemical composition of Musca domestica products. An overview of average values, the reported range, and number of entries can be found in Table 2 (in alphabetical order: Adewolu et al, 2010;Ajani et al, 2004;Akpodiete et al, 1997;Aniebo et al, 2008;Aniebo & Owen, 2010;Aniebo et al, 2009;Awoniyi et al, 2003;Barroso et al, 2014;Calvert et al, 1969;Fasakin et al, 2003;Hall et al, 2018;Hwangbo et al, 2009;Ido et al, 2015;Leyo et al, 2022;Mustapha & Kolawole, 2019;Ocio et al, 1979;Odesanya et al, 2011;Ogunji et al, 2008;Ogunji et al, 2009;Okah & Onwujiariri, 2012;Pretorius, 2011;Sogbesan et al, 2006;Ukanwoko & Olalekan, 2015;Wang et al, 2017b;Zuidhof et al, 2003). As not all studies detailed development stage, and sometimes stages were combined, the summarized data pertain to house fly larvae, pupae or mixtures thereof.…”
Section: Composition Of House Fly Reared On Pure Manure and Manurebas...mentioning
confidence: 99%
“…Processed house fly larvae are highly suitable for animal diets in the livestock and the aquaculture sector due to their high protein content and balanced essential amino acids profile (Makkar, 2014). The application of maggot meal has been extensively studied in poultry as a replacement of fish meal (Teguia et al, 2002;Awoniyi et al, 2003;Agunbiade et al, 2007;Okah & Onwujiariri, 2012;Hall et al, 2018), and as a supplement (Dankwa et al, 2002;Hwangbo et al, 2009). House fly larvae supply more than twice the crude protein requirements of 1-4 weeks old turkey (NRC, 1994) and more amino acids than the soya bean meal composition reported by NRC (1994) (Zuidhof et al, 2003).…”
Section: Livestock and Aquaculturementioning
confidence: 99%
See 1 more Smart Citation